2016
DOI: 10.5194/se-7-1509-2016
|View full text |Cite
|
Sign up to set email alerts
|

Feathery and network-like filamentous textures as indicators for the re-crystallization of quartz from a metastable silica precursor at the Rusey Fault Zone, Cornwall, UK

Abstract: Abstract. Hydrothermal quartz crystals, which occur in the Rusey Fault Zone (Cornwall, UK), show feathery textures and network-like filamentous textures. Optical hot-cathodoluminescence (CL) analysis and laser ablation inductively coupled plasma mass spectrometry (LA-ICP-MS) investigations on quartz samples revealed that positions exhibiting feathery textures (violet luminescence) contain higher amounts of Al and Li than quartz positions without feathery textures (blue luminescence), while concentrations of Al… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
3
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 49 publications
3
3
0
Order By: Relevance
“…It is worth noting that the positive correlation between Al and Li in the hyaline quartz (and chalcedony) from the investigated sample. Similar relationship has been reported by i.e., Yilmaz et al (2016) or Perny et al (1992) and can be attributed to Si ↔ Al(+ Li) substitution in the crystal lattice during the crystal growth in hydrothermal environment. Moreover, according to this author, the presence of feathery quartz may also account for variable amounts of Al and Li in hydrothermal quartz.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…It is worth noting that the positive correlation between Al and Li in the hyaline quartz (and chalcedony) from the investigated sample. Similar relationship has been reported by i.e., Yilmaz et al (2016) or Perny et al (1992) and can be attributed to Si ↔ Al(+ Li) substitution in the crystal lattice during the crystal growth in hydrothermal environment. Moreover, according to this author, the presence of feathery quartz may also account for variable amounts of Al and Li in hydrothermal quartz.…”
Section: Discussionsupporting
confidence: 89%
“…The hydrothermal Bambauer quartz with typical µm-sized growth lamellae indicates a lower temperature of hydrothermal fluids characterized by strong fluctuations in silica concentrations and/or pH conditions (Bambauer et al 1961;Richter et al 2015;Powolny et al 2019;Götze et al 2020;Pršek et al 2020) or episodic crystallization, with periods of stasis alternating with periods of growth. Lastly the local evidence of feathery/splintery extinction of some quartz crystals agrees with subsequent recrystallization of metastable silica phases such as chalcedony or amorphous silica (Fournier 1985;Yilmaz et al 2016;Powolny et al 2019;Götze et al 2020;Pršek et al 2020).…”
Section: Discussionmentioning
confidence: 55%
“…In their study, Zn, Cu, Ca, and iron were reported to be at higher levels of accumulation in the fish liver (38), similar to the results obtained for the Cu and Fe in the present study. The results of the present study are also consistent with the results of a study conducted by Yilmaz et al (39) who investigated the element accumulations in the tissue of Tinca tinca. They found that the Cu and Fe levels in the fish liver were higher than in other tissues.…”
Section: Tissue Element Analyses In Alosa Braschnikowisupporting
confidence: 93%
“…The presence of boiling could be further responsible for the formation of ore-related phases, such as Fe and Cu sulfides found within the silica matrix of agates. The feathery and jigsaw puzzle quartz microtextures found within agate nodules provide, in turn, strong evidence for the recrystallization of pre-existing massive chalcedony or amorphous silica [52][53][54].…”
Section: Discussionmentioning
confidence: 99%